If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 17 = 43 Reorder the terms: 17 + 2w = 43 Solving 17 + 2w = 43 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 2w = 43 + -17 Combine like terms: 17 + -17 = 0 0 + 2w = 43 + -17 2w = 43 + -17 Combine like terms: 43 + -17 = 26 2w = 26 Divide each side by '2'. w = 13 Simplifying w = 13
| h=-16t^2+77t+77 | | x(x+8)=180 | | 112-6x=12x+18 | | 12-4x=15-3x | | 5x^2+37+42=0 | | 6x+9y=36 | | 5x^2+37=-42 | | 3-1.2y=2.4 | | 8x^(7/2)-24=0 | | 7/2y-1+13 | | m=-0.5(29)+23 | | 5x+3=19+5 | | 2x^2+18=90 | | 4x^2-31x+21=0 | | 9-7x=90-28x | | 159-2x=34x+23 | | 2(3x+4)=4x-2 | | x(2x-1)*(3x+2)=0 | | x^4-24x^3+144x^2=0 | | 8+2x+3-x=2x-1 | | 4x-12x+9=0 | | x^4-24x^3+14x^2=0 | | -39+r=26 | | =4y^3-4y^2+3-y | | 11-8x=147-36x | | (7x^2)+24=54 | | x^3+x=332.5 | | (20+p)+(3p-23)+p=552 | | 11x=3x^2-4 | | 45=3(w-36)+30 | | X+x+12+x+x+12=x+11+x+11+x+16 | | 4(k+10)+k= |